Analisis Struktur Modal, Pertumbuhan Perusahaan, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan pada Perusahaan Makanan dan Minuman - Eko Yuliawan; Cintia Ayu Kartika; Sulastri Sulastri (Journal of Academia Perspectives, 2022)
This study aims to determine how much influence capital structure, firm growth and managerial ownership have on firm value in food and beverage companies listed on the Indonesia Stock Exchange in 2016 – 2018. The population in this study amounted to 26 food and beverage companies listed on the stock exchange. Indonesia. The research method carried out by the author in this study is associative research, because it will examine the causal relationship of two or more variables using the data collection technique used is purpose sampling and data obtained as many as 12 companies. The technique used is quantitative analysis with multiple linear. The results of this study were conducted on food and beverage companies listed on the Indonesia Stock Exchange in 2016 – 2018 with an F value of 12.204 which is greater than the specified level of 0.05 indicating that the Debt to Equity Ratio (DER), Company Growth (Growth) and Managerial Ownership (KM) simultaneously or jointly has a positive and significant effect on Company Value. The results of the t test show that the capital structure variable (DER) has no positive and significant effect on firm value, as evidenced by a significance value of 0.750, which is greater than the specified significant, which is 0.05. Company growth has no positive and significant effect on firm value, as evidenced by a significance value of 0.814, which is greater than the expected significance value of 0.05. and managerial ownership has a positive and significant effect on firm value as evidenced by a significance value of 0.000 which is smaller than the expected significance of 0.05 in food and beverage companies listed on the Indonesia Stock Exchange in 2016 – 2018.